A prospective observational study investigating all children presenting to a specialty paediatric burns centre. Issue 3 (May 2015) - Stockton, K.A.; Harvey, J.; Kimble, R.M.
Highlights Outpatient paediatric burns are under reported. Scalds are the most common mechanism of burn injury in paediatrics in Queensland. Flame burns are over represented and contact burns under represented in paediatric inpatients.